Effects of Methotrexate on Prothrombin Time in Rheumatoid Arthritis Patients (KYAMC Journal, 2017)
The present study was undertaken to evaluate safety and efficacy of methotrexate in Rheumatoid arthritis patients. This study was carried out on ARA criteria fulfilling 35 diagnosed Rheumatoid arthritis patients of either gender, aged 20-60 years, presented in Medicine department of Rajshahi Medical College Hospital, Rajshahi from July 2007 to June 2008. Patients with normal liver function tests and HBsAg and anti-HCV negative cases were given oral methotrexate (10-15 mg/wk) for 6 weeks. Baseline prothrombin time was 12.97±0.34 seconds. After 6 weeks of methotrexate therapy prothrombin time was found 13.47±0.46 seconds. During methotrexate therapy change of prothrombin time was not significant (p>0.05).KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 550-552